Change to reform: new curriculum guidelines for the training of psychologists in San Marcos - García A., Lupe (2006)
It exposes the conclusions and recommendations of the Curricular Seminary 2006, that concludes in the curricular reform for formation of psychologist in Universidad Nacional Mayor de San Marcos. The event was carried out in the months of May, June, July and August, oriented under orientacin of vision and mission raised by one Comision Transitory. The raised vision had the following content, «to obtain a curricular system for the university professional formation of the psychologist, who viabilice and guarantees the way towards the university accreditation in the scopes national and international», and the mission, «to fulfill the requirements that the academic excellence demands, developing an efficient curricular management, that allows the change for a university formation, of professional quality that responds to the expectations of the psychological community and the Peruvian nation».